Some aspects of the significance of the Convention on human rights protection and fundamental freedoms and practice of the European court on human rights for the understanding of private life as the object of criminal law protection - Дем’яненко, Юлія Іванівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
Article is devoted to consideration of some questions of value of provisions of the Convention on human rights protection and fundamental freedoms and practice of the European court on human rights in a context of ensuring criminal law protection of inviolability of private life (Art. 182 CC of Ukraine).